Internet Access and Use in Latin America and the Caribbean : From the LAC High Frequency Phone Surveys 2021 - World Bank (World Bank, Washington, DC, 2022)
While most households in Latin America and the Caribbean use mobile broadband via smartphones, expensive fees and poor service quality pose major obstacles for potential users. In addition, power outages are a challenge for nearly 40 percent of existing mobile broadband users. Addressing the region’s need for faster, cheaper, and more reliable internet connections is thus a policy and investment priority. There are persistent and significant gaps in digital infrastructure between countries in the region, as well as weighty rural-urban gaps within some countries. Bridging these digital divides will be key to inclusive digital transformation. Households with tertiary education are on average more connected (with better quality service and higher expenditures on data) compared to the rest of the population. As education level is correlated with income, digital inequalities mirror and may amplify existing social inequalities – underscoring the critical need to address them. Over two-thirds of connected households in the region are concerned about privacy and security when using the internet. However, households on average across Latin America and the Caribbean still reported increasing their use of the internet amid the pandemic, suggesting that neither issue poses a barrier to their internet use at present.